Violência conjugal contra a mulher na perspectiva dos homens encarcerados por essa prática no Complexo Prisional de Aparecida de Goiânia-GO - Sousa, Gaspar Alexandre Machado de (2017)
This thesis deals with conjugal violence against women from the perspective of men imprisoned by this practice in the Prison Complex of Aparecida de Goiânia-GO. It is a study characterized as a qualitative approach, whose central question is to understand whether the imprisonment by the Maria da Penha Law influences the way in which men signify conjugal violence against women. In order to answer this question, a bibliographical survey was first made based on the theoretical framework chosen for the conceptualization of "gender", "power", "masculinity", "violence" and "stigma". Subsequently, semi-structured interviews were carried out with thirty men imprisoned in the said Prison Complex for the practice of conjugal violence against women. The files and records of the criminal proceedings to which the interviewees respond were also examined. After the interviews, there was a categorization of the subjects' speeches, which subsidized the analysis undertaken in the thesis. Based on this categorization, which was based on the sociological concepts worked, the following nuclei of interest were defined: a) marital relationship; b) conjugal violence; c) Maria da Penha Law, prison and prospects for the future. For the analysis of the interviewees' speeches, the discourse analysis technique was used. It was concluded that the imprisonment under the Maria da Penha Law does not influence the way in which men signify conjugal violence against women. On the contrary, in seeking criminalization as an end in itself, current legislation does not bring about change, it only breeds the reproduction of traditional ideals, reinforcing the convictions that led men to practice violent behavior. Obviously, it is not disputed that the safety of women in situations of violence is fundamental, so that all aggression must be stopped and its perpetrator blamed. However, this is not simply to restrict the complexity of violent conjugal interactions to the criminal dimension. It is urgent, therefore, to broaden the discussions on the best ways to overcome domestic and family violence against women, beyond the penal system.